Reliability of the tissue microarray based FISH for evaluation of the HER-2 oncogene in breast carcinoma. Issue 4 (1st April 2002) - Gancberg, D; Di Leo, A; Rouas, G; Järvinen, T; Verhest, A; Isola, J; Piccart, M J; Larsimont, D
Abstract : Aims: Tumour tissue microarray allows the analysis of hundreds of tumour samples simultaneously on a single microscope slide. However, the extremely small tissue samples taken from the original tissue may not always be representative of the entire tumour. Methods: The reliability of this new technology was investigated by analysing HER-2 oncogene amplification by fluorescence in situ hybridisation (FISH) from representative slides of the whole tumour and small tissue core biopsies from 29 invasive breast tumours. Results: The tissue microarray method had high accuracy; in only one of 29 cases (3.4%; 95% confidence interval, 0% to 10%) were the results discordant with whole tumour analysis. Conclusion: Tumour microarray is a highly reliable method for analysing HER-2 oncogene amplification by FISH in human breast tumours.